2018
DOI: 10.1186/s12910-018-0293-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical informed consent in obstetric and gynecologic surgeries: experience from a comprehensive teaching hospital in Southern Ethiopia

Abstract: BackgroundSurgical Informed Consent (SIC) has long been recognized as an important component of modern medicine. The ultimate goals of SIC are to improve clients’ understanding of the intended procedure, increase client satisfaction, maintain trust between clients and health providers, and ultimately minimize litigation issues related to surgical procedures. The purpose of the current study is to assess the comprehensiveness of the SIC process for women undergoing obstetric and gynecologic surgeries.MethodsA h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
41
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 13 publications
10
41
4
Order By: Relevance
“…Three studies recommended strategies to improve the process of obtaining informed consent. 26 28 The 4 recommended strategies were using visual aids such as videos, providing a context for the surgery based on the patient’s everyday life (eg, explaining how will the recovery affect a patient’s ability to work or how long they will need to stay away from their family), making the patient repeat the most important points, and pausing after each point.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies recommended strategies to improve the process of obtaining informed consent. 26 28 The 4 recommended strategies were using visual aids such as videos, providing a context for the surgery based on the patient’s everyday life (eg, explaining how will the recovery affect a patient’s ability to work or how long they will need to stay away from their family), making the patient repeat the most important points, and pausing after each point.…”
Section: Resultsmentioning
confidence: 99%
“…Ochieng et al 23 found that 34% of the study participants, who were doctors from 3 Ugandan teaching hospitals, did not know the definition of informed consent. Teshome et al 28 found that doctors at a university hospital in Ethiopia did not include the majority of essential information required to obtain informed consent for obstetric and gynecological surgeries. On average, they only managed to consent patients for 4.5 out of 13 essential domains necessary to gain valid informed consent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, a sample size calculation was not performed due to absence of prevalence data on informed consent recollection in our setting or similar populations in the designing phase of the study. At the time of finalising this paper, such data are available 7 8. Our sampling was based on convenience and logistical possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have recognised weaknesses in the process of acquiring surgical informed consent for obstetric procedures, such as providing no explanation of the indication for surgery, procedure-related risks or the postoperative trajectory 7–16. Women may feel pressured into undergoing surgery when little information is provided or information is not understood 9 14.…”
Section: Introductionmentioning
confidence: 99%